Afropolitan Horizons Essays toward a Literary Anthropology of Nigeria - Hannerz, Ulf (Berghahn Books, 2022)
Nigeria is a country shaped by internal diversity and transnational connections, past and present. Leading Nigerian writers from Chinua Achebe, Amos Tutuola and Wole Soyinka to Chimamanda Ngozi Adichie and Teju Cole have portrayed these Nigerian issues, and have also written about some of the momentous events in Nigerian history. Afropolitan Horizons discusses their work alongside other novelists and commentators, as well as describing the ways in which Nigeria has appeared in foreign news reporting. It is all interwoven with the author's own anthropological field research in a town in Central Nigeria.